Geospatial analysis of dengue emergence in rural areas in the Southern Province of Sri Lanka. (24th December 2019) - Mutucumarana, Charmaine P; Bodinayake, Champica K; Nagahawatte, Ajith; Devasiri, Vasantha; Kurukulasooriya, Ruvini; Anuradha, Thamali; De Silva, Aruna Dharshan; Janko, Mark M; Østbye, Truls; Gubler, Duane J; Woods, Christopher W; Reller, Megan E; et al.
Abstract: Background: Dengue is a major cause of acute febrile illness in Sri Lanka. Dengue has historically been considered an urban disease. In 2012–2013, we documented that acute dengue was surprisingly associated with self-reported rural residence in the Southern Province of Sri Lanka. Methods: Patients admitted with an acute febrile illness were enrolled from June 2012–May 2013 in a cross-sectional surveillance study at the largest tertiary care hospital in the Southern Province. Acute dengue was diagnosed by serology and virology testing. Site visits were performed to collect residential geographical coordinates. Spatial variation in odds of acute dengue was modeled using a spatial generalized additive model predicted onto a grid of coordinate pairs covering the Southern Province. Results: Of 800 patients, 333 (41.6%) had laboratory-confirmed acute dengue. Dengue was spatially heterogeneous (local probability of acute dengue 0.26 to 0.42). There were higher than average odds of acute dengue in the rural northeast of the Southern Province and lower than average odds in the urbanized southwest of the Southern Province, including the city Galle. Conclusions: Our study further affirms the emergence of dengue in rural southern Sri Lanka and highlights both the need for real-time geospatial analyses to optimize public health activities as well as the importance of strengthening dengue surveillance in non-urban areas.